Efektivitas Krib Untuk Mengurangi Gerusan Di Tikungan Luar Sungai Bengawan Solo - James Zulfan; Yiniarti Eka Kumala (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2018)
Bengawan Solo River considered as a meander river. This condition has potentially triggered local scouring due to high flow velocity at the outer bend of the river. The scouring phenomenon occur in the segment of of Bengawan Solo river in junction with Kali Pepe river where the river bank has shifted ± 2 meter. This condition indicates that the erosion and scouring have occurred and need immediate scenarios because the river banks was eroded and the nearby residential areas wa threaten. To protect the critical river banks, groyne structure was implemented. This study aims to investigate the effectiveness of the placing of groyne structure along the outer river bend using 3 dimensional physical model test at the Hydraulics Laboratory. The obtained resutls will be verified by 2 dimensional numerical modeling. Based on the physical hydraulic model testing, groyne and riprap setup with optimum distance can be effective to reduce the energy and flow velocity of the river flow to secure the dikes and river embankments.